2006
DOI: 10.1152/japplphysiol.00348.2006
|View full text |Cite
|
Sign up to set email alerts
|

The effect of surface electrical stimulation on hyolaryngeal movement in normal individuals at rest and during swallowing

Abstract: Surface electrical stimulation is currently used in therapy for swallowing problems, although little is known about its physiological effects on neck muscles or swallowing. Previously, when one surface electrode placement was used in dysphagic patients at rest, it lowered the hyolaryngeal complex. Here we examined the effects of nine other placements in normal volunteers to determine 1) whether movements induced by surface stimulation using other placements differ, and 2) whether lowering the hyolaryngeal comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
147
1
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(163 citation statements)
references
References 17 publications
(21 reference statements)
6
147
1
4
Order By: Relevance
“…However, only a few attempts have been made to elicit swallowing with electrical stimulation in humans, [43][44][45] and each of the methods has problems such as limited stimulation sites and difficulty in adjusting the electrode position. Therefore we tried to establish an effective way eliciting swallowing using electrical stimulation in humans.…”
Section: Factors Modulating Swallow Initiation In Humansmentioning
confidence: 99%
“…However, only a few attempts have been made to elicit swallowing with electrical stimulation in humans, [43][44][45] and each of the methods has problems such as limited stimulation sites and difficulty in adjusting the electrode position. Therefore we tried to establish an effective way eliciting swallowing using electrical stimulation in humans.…”
Section: Factors Modulating Swallow Initiation In Humansmentioning
confidence: 99%
“…In the treatment of dysphonia there was a decrease in the size of laryngeal lesions, dysphonia degree of improvement, increased TMF and glottal closure hyoid bone excursion during swallowing, however, two weeks after the end of treatment the gain was not sustained. In the study 35 which evaluated 10 local application of electrical stimulation, described three local application did not produce the hyoid descent during rest and, on the elevation of the hyoid bone, there was a gain in elevation of the hyoid with swallowing effort. Seven of the eight subjects evaluated in a survey 36 they showed no significant gains with the use of NMES on myoelectric activity of the larynx.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies with evidence levels 2B [34][35][36] They tested the effect of electrical stimulation applied to the submental and laryngeal muscles of healthy subjects to evaluate the effect of NMES on the elevation of the hyoid during swallowing, examine the effect in 10 sites of application of NMES applied to the submental area for two weeks and see if It would have increased myoelectric activity of the larynx. In one study 34 , there was an increase of the patients, but studies with higher levels of evidence must be carried out, especially with a large sample and with a more homogeneous group of patients, to then check your results.…”
Section: Electrostimulation Of the Effect On Swallowing Biomechanics mentioning
confidence: 99%
“…VitalStim TM has gained popularity as a transcutaneous NMES to improve hyolaryngeal movement, although research has reported substantially limited to no benefits on swallowing ability [e.g., 86,87]. Additionally, negative effects of VitalSim TM such as significant hyoid depression have been identified [88,89]. In studies in which improvement in swallowing has been identified [90], VitalStim TM was paired with effortful swallow for 1 h sessions completed 5 days per week for 3 weeks.…”
Section: Rehabilitation Adjunctsmentioning
confidence: 99%